Pengembangan Skala Kebersyukuran: Uji Validasi dan Reliabilitas - Hidayati, Diajeng Laily; Purwandari, Eny (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Gratitude is one of the positive emotions closely linked to an individual's psychological well-being. Individuals who perceive and approach problems or suffering positively are more capable of enduring and overcoming such challenges. HIV is a disease for which a cure has not yet been found. Therefore, an assessment of gratitude among People Living with HIV (PLHIV) is necessary to formulate more precise psychological interventions. Testing the validity and reliability of this gratitude measurement scale can significantly contribute to research, evaluation, or intervention efforts related to feelings of gratitude within the population of PLHIV. The researcher obtained responses from 232 participants, with the majority being male aged 25-49, accounting for 59.05%, and the majority having completed high school education, totaling 56.90%. After undergoing psychometric testing, including assessments of internal consistency and construct validity, it can be concluded that the gratitude scale used in this study demonstrates good validity and reliability. This scale consistently measures the same concept and has been validated in assessing gratitude through three main factors: sense of appreciation, positive feelings, and expressions of gratitude.